MODAL INTELEKTUAL SEBAGAI DETERMINAN KINERJA PERUSAHAAN - Lutfillah, Novrida Qudsi; Sukmana, Nour Kholifah (Widya Mandala Surabaya Catholic University, 2018)
This study aims to determine the effect of Intellectual Capital on the company's financial performance. This study uses the Pulic Model (Value Added Intellectual Coefficient - VAICTM) as a measure of efficiency in the Intellectual Capital component and Double Linear Regression (R2) are used to examine the relationship between VAICTM and corporate financial performance. The results of this study indicate that: VACA has a partial effect on ROA; VAHU has no partial effect on ROA; STVA has a partial effect on ROA and VACA, VAHU, STVA allegedly influencing jointly or simultaneously to the ROA.